Nurses’ voices used to heighten fears of fentanyl exposure in British Columbian rural hospitals / La voix du personnel infirmier instrumentalisée pour amplifier les peurs liées à l’exposition au fentanyl dans les hôpitaux ruraux de la Colombie-Britannique - Hodgson, Kate; Lavigne, Amanda; Bardwell, Geoff (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence)

(untitled) (Pappin Communications, 2025)
People who use drugs (PWUD) experience stigma when accessing hospital-based healthcare, including emergency care. Rural settings are of particular concern, due to heightened social-structural stigma toward PWUD in smaller communities. These barriers have been exacerbated further by recent narratives in media and political attention on the risks to healthcare providers when exposed to PWUD using substances while in hospital. Nurses’ voices have been used directly and indirectly to influence political discourses to raise moral panic regarding workplace exposure to second-hand smoke from unregulated substances (e.g., fentanyl and methamphetamine). Immediate collective nursing action is required to protect nurses’ professional and ethical obligations and ensure safe and stigma-free access to hospital care for rural PWUD in the current political climate in British Columbia, Canada.